2016
DOI: 10.1590/0102-7786312314b20150105
|View full text |Cite
|
Sign up to set email alerts
|

Uso do Modelo WRF-CHEM para a Simulação da Dispersão de Gases no Centro de Lançamento de Alcântara.

Abstract: Resumo O presente trabalho utiliza o modelo Weather Research and Forecasting (WRF) acoplado ao seu módulo químico para simular a dispersão dos poluentes emitidos por um Veículo Lançador de Satélites (VLS) lançado a partir do Centro de Lançamento de Alcântara (CLA). Para inserir os dados químicos no modelo foi utilizado o pré-processador PREP-CHEM. As simulações foram feitas para 4 casos a saber: casos dos períodos diurnos e noturnos durante as estações seca e chuvosa. Identificaram-se as regiões afetadas pela … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These cases are summarized in Table 4. In these periods, there were no anomalies of climatic conditions (such as temperature, precipitation, wind or humidity) in the state of Maranhão, representing the synoptic conditions typical for both dry and rainy seasons (Iriart & Fisch, 2016).…”
Section: Data and Simulated Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…These cases are summarized in Table 4. In these periods, there were no anomalies of climatic conditions (such as temperature, precipitation, wind or humidity) in the state of Maranhão, representing the synoptic conditions typical for both dry and rainy seasons (Iriart & Fisch, 2016).…”
Section: Data and Simulated Resultsmentioning
confidence: 96%
“…Table 6 shows a summary of the concentration peak (from simulations) and atmospheric state (from observed data) for all simulated cases. The peak concentration for each site is presented first, followed by the transport time from the plume, wind speed and direction, and the turbulent intensity (σ U /U, where σ U is the standard deviation of the wind speed) calculated at levels of 10 and 60 m with an anemometer tower data installed at the SPL, close to the TMI (Iriart & Fisch, 2016).…”
Section: Data and Simulated Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, such analyses are of great importance in the cases of launching accidents that would result in larger amounts of pollutant gases. Iriart and Fisch (2016) and Schuch and Fisch (2017) observed that the wind advection is a major meteorological factor that influences the pollutants dispersion at the ALC. Therefore, the knowledge of the flow pattern is essential to establish the atmospheric dispersion conditions to which the ALC is exposed and provide the necessary basis for studies of the dispersion of pollutants emitted during rocket launches.…”
Section: Introductionmentioning
confidence: 99%